Strategic Cropping Plans for Horticultural Crops in the unique Agro-Climatic conditions of the Kashmir valley - wagay, Rouf Ahmad; Mohd Imran,; Ganaie, Irfan Hassan (International Journal of Psychosocial Rehabilitation, 2019)
The Kashmir Valley presents unique agro-climatic conditions that demand strategic cropping plans for horticultural crops to maximize productivity and resilience. This paper synthesizes existing research and local expertise to propose tailored strategies for optimal crop selection, planting schedules, and management practices. Factors such as altitude, temperature variations, precipitation patterns, soil types, and market demand are considered in designing adaptable cropping plans. Emphasis is placed on diversification, crop rotation, and integrated pest management to enhance sustainability and mitigate risks associated with climate variability. Additionally, the socioeconomic context and the potential for value addition through processing and marketing are explored to foster resilience and prosperity among local farmers. The proposed strategic cropping plans aim to empower farmers with knowledge and tools to navigate the complexities of Kashmir's agro-climate while fostering environmentally sustainable and economically viable horticultural production systems. Horticulture being one of the vibrant sector of economy in state provides employment opportunities to about half of population. Out of total area of horticulture in state, 90 per cent is in Kashmir valley. Due to continuous increase in production and export, agricultural land is getting diversified into horticultural land. Horticulture directly influences the income, employment and living standard in rural areas of valley. The diverse agro climatic condition of the Kashmir valley offers great potential for growing various varieties of temperate fruits like Apple, Pear, Peach, Plum, Cherry, Walnut and Almond. With the emergence of urbanisation and modernisation change in cropping pattern from traditional to cash rich crops has made horticulture one of the important industry in Kashmir valley.